Closure and survival in Sindiwe Magona's Living, Loving And Lying Awake At Night (1991) - Callahan, David (Africana Studia, 2020)
Sindiwe Magona's Living, Loving and Lying Awake at Night (1991} deals with the unspectacu!ar, the daily, the details of family and working life, in her case the details of the lives of Xhosa women not directly involved in the politica! struggle but rather in the more pressing struggle for material survival in contemporary South Africa. ln carrying out this project Magona tends to utilise the strategies of literary realism, the speaking voice that does not interrogate its ontological or hermeneutic status, which has always been important for a literature of witness. The article considers the relation between the realist literary strategy of closure and the discourse of survíval in Magona's stories.